2011
DOI: 10.1080/02642060902960784
|View full text |Cite
|
Sign up to set email alerts
|

Organisational rigidities and marketing theory: examining the US department store c.1910–1965

Abstract: By analysing the US department store between c. , this article deepens our understanding of the nature of the transition to phases of 'maturity' and 'decline' that are fundamental to models of retail change (retail wheel, retail life-cycle). By employing a close reading of key marketing and management writing of the period, it finds that "lockin" to an organisational structure associated with a single downtown store posed significant obstacles to suburban branched expansion. Only partial organisational central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Studies on the history of retailers and retail structure show mixed support for this model. Wood [8] finds support for the wheel of retailing in explaining the rise of the department store in the United States from 1920-1965, essentially steps 1-2 in Figure 1. Other researchers note that the market power of large firms has created barriers to market entry for innovative and low cost retailers in the past [16] and that some retail firms start at step 2, as specialty stores and department stores offering greater service and more expensive merchandise [10].…”
Section: Figurementioning
confidence: 96%
See 2 more Smart Citations
“…Studies on the history of retailers and retail structure show mixed support for this model. Wood [8] finds support for the wheel of retailing in explaining the rise of the department store in the United States from 1920-1965, essentially steps 1-2 in Figure 1. Other researchers note that the market power of large firms has created barriers to market entry for innovative and low cost retailers in the past [16] and that some retail firms start at step 2, as specialty stores and department stores offering greater service and more expensive merchandise [10].…”
Section: Figurementioning
confidence: 96%
“…Other researchers such as Evans [23] argue that the wheel of retailing forces organizations to consider how they will adapt to both competition and market conditions, as there are always emerging opportunities for growth from rival firms at both the high and low cost end. What is not clear, apart from historical analysis [4,8], is how the movement of the wheel can be affected by the advent of shopping malls and competition from online retailers. The object of the paper is to get a deeper understanding of this by applying a simulation of an ecosystem, which has competing species with differential growth rates, to the retail landscape of shopping malls.…”
Section: Vulnerabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Path dependence contributes to our understanding of cumulative causation, with the observation that "extraneous features of the initial conditions, the historical context in which organizations are formed, can become enduring constraints" (David 1994, p. 214). Indeed, in his study of US department stores from 1910-1965, Wood (2011 found "lockin" to the traditional downtown locations "posed significant obstacles" to adaptation and progress, and contributed to their ultimate decline.…”
Section: Environmental Influencesmentioning
confidence: 99%